Legitimacy or efficiency? Carbon emissions transfers under the pressure of environmental law enforcement. (10th September 2022) - Pan, Lipeng; Han, Wenqi; Li, Yongqing; Wu, Hanxu
Abstract: Reducing the carbon footprint of companies will be essential if we are to stabilise climate change. However, many researchers are concerned that companies will simply transfer their carbon emissions to another party resulting in carbon leakage rather than emissions reduction. Thus, there is a need to thoroughly investigate what drives companies to transfer carbon emissions as opposed to reducing them. In this study, we explore the motivations and internal mechanisms behind a company's decision to opt for carbon transfers instead of carbon reduction. Drawing on legitimacy theory with a US sample, we provide evidence that strict environmental laws are an external motivation that place pressure on companies to transfer their carbon emissions. Using overseas capital and declared emissions reductions as a proxy for carbon emissions transfer, we find a significant positive correlation to environmental law enforcement. In addition, when facing the force of environmental law, the carbon strategies companies choose are influenced by a felt pressure to operate with both legitimacy and efficiency. Moreover, as pressure mounts in either of these spheres, companies become more and more likely to opt for emissions transfer not emissions reduction. The results indicate that strict environmental regulations forces companies to transfer carbon emissions, which is exacerbated if companies have a high legitimacy and efficiency pressure. As such, this study provides an in-depth discussion on corporate responses to carbon emissions with valuable implications for carbon emissions policymakers.